(untitled) (Contemporary Journal of Social Science Review, 2025)
Realizing the importance of chemistry in daily life, has become the compulsory part of education and science education all over the world. Johnstone drew attention to the existence of the three levels of chemistry: macroscopic, sub-microscopic and symbolic. These levels can be represented in the form of a triangle. The current study aims to assess the secondary school students’ chemical knowledge across levels and sub-concepts. The students’ data was collected through convenient sampling from public and private schools of Lahore. The data is analyzed applying independent sample t-test. The major findings of the study illustrate that students have high understanding at macro and symbolic level of chemical knowledge than sub-micro level. It is recommended that chemical education should be carved level wise from secondary to higher level of studies.